Trójkąt Weimarski w latach 1991–1999 i jego znaczenie dla bezpieczeństwa europejskiego - Bąk, Maciej (Przegląd Strategiczny, 2013)
The aim of the article is to analyze theWeimar Triangle’s influence on the European security, focusing on the Polish-German and French-German relations, as they play a key role in forming a geostrategic and geopolitical structure in the European context. The way in which the European Union’s member states cooperated with Poland is a symbol of reconciliation for those three great nations. The objective of this initiative was to transform an area of the bygone fierce European wars into a pillar of the continent’s security. According to the author, theWeimar Triangle may serve as a perfect example of how the differences between the Central andWestern Europe in terms of the standards of living could be reduced and how the technological and civilizational gulf could be neutralized in order to guarantee peace and stability in the whole of Europe. Nowadays, the foundation and development of ESDP/CSDP is a chance for good inter-ally relations, while the most serious challenges for the Triangle’s countries include dealing with both the eastern policy and energy policy.